Reduction of Residual Stress for High-Strength Low-Alloy Steel Strip Based on Finite Element Analysis - Zengshuai Qiu; Anrui He; Jian Shao; Xiaoming Xia (Advances in Materials Science and Engineering)
Intensive cooling technology is widely utilized in the production of high-strength hot-rolled steel strip. However, intensive cooling at high cooling rate may cause stress heterogeneity on a steel strip, which further generates great residual stress and influences steel strip shape. In this study, a three-dimensional finite element (FE) model of high-strength low-alloy steel strip on the run-out table coupled with heat transfer, phase transformation, and strain/stress is developed by ABAQUS software. To enhance modeling precision, several experiments are conducted, such as uniaxial tensile test at multiple temperatures, dynamic continuous cooling transformation, and scanning electron microscopy, to determine the material properties and boundary conditions of the FE model. Four new models are established based on this model to reduce the residual stress of strip by modifying the initial and boundary conditions. Results show that reducing the initial transverse temperature difference is the most effective in reducing residual stress, followed by sparse cooling, edge masking, and posterior cooling.